Knowledge regarding Dietary Pattern among Female Adolescents of a Secondary School, Bhaktapur - Rai, Janaki (Journal of Nursing Education of Nepal, 2023)
Adolescence marks a time of rapid and intense emotional and physical changes. There is  increase value placed on peer acceptance and approval. During this development phase,  a adolescent girl begins to focus on their physical appearance. The experience of body  dissatisfaction can lead to poor health habits associated with poor eating habits, dieting and  severe eating disorder for the purpose of losing body weight and to achieve specific body  image leading to various nutritional deficienfy disorders.This research was conducted to  assess the Knowledge and Attitude regarding Dietary Pattern among Adolescent Girls.  The design of the study was descriptive in nature which was carried out in secondary school  of Madhyapur Thimi, in Bhaktapur district. In this study 100 Samples of class 8, 9 and 10  were selected by using non- probability purposive sampling method. A semi-structured,  self administered questionairs were used for data collection and analysis was done by using  descriptive statisistics. In this study majority of the adolescents had knowledge about the beneficial and non beneficial  food items. According to finding, all of the respondents(100%) expressed that chapati, mango  are benificial and Icecream is nonbenificial. Similarly majority of respondents (88%) had  expressed that hot drinks are benificial than cold drinks (90%). Majority of the respondents  (86%) think that exercise is the best way to control overweight whereas 60% of them think  that dieting helps to maintain body figure . Fot this 30% of them prefer to skip lunch, dinner  (10%) and break fast(8%).Similary they also prefered lemon water(26%), water(20%), tea  and coffee(12%) and nothing by mouth(12%) respectively. From this study, it is concluded that knowledge regarding dietary pattern among adolescents  is good even though they prefer to skip the foods by supplimenting it by non food to maintain  their body figures.
Keywords: Dietary pattern; Adolescent; Skipped Meals; Knowledge